COMPARATIVE EVALUATION OF SURGICAL CORRECTION METHODS OF VESICO-URETERIC REFLUX IN CHILDREN - S. P. Yatsyk; А. G. Burkin; S. М. Sharkov; К. S. Abramov; А. А. Rusakov; I. F. Tin ("Paediatrician" Publishers LLC, 2014)
Background: To compare different surgical correction methods of vesico-ureteric reflux in children using both open surgery and endoluminal (intraluminal) treatment options of this pathology. Patients and methods: 166 patients aged from 4 months to 13 were examined and treated. All children underwent X-ray urological examination through cystography and ultrasound examination of kidneys and urocyst. Cohen's operation, STING procedure involving endoscopic injection of bulking agents was performed. Treatment results were assessed 6 months later through control cystography. Conclusion: Endoscopic correction of vesico-ureteric reflux is an effective and minimally invasive treatment method for this pathology. Maximum treatment effect after biodegradable bulking agents application should be expected in younger age group. Treatment rates of endoluminal correction of vesico-ureteric reflux with the use of sterile viscous gel as a fixing agent are higher than with the use of bovine collagen.